Women at work: The status of women in the labour markets of the Czech Republic, Hungary and Poland - Éva Fodor (United Nations Research Institute for Social Development (UNRISD), 2005)
This paper assesses trends in women's labour-market positions in three Central European countries from 1989 to 2002: Hungary, the Czech Republic and Poland. I also examine how these changes are related to-affect, are derived from and have consequences for-the reformulation of women's social rights, especially those concerning women's responsibilities in childbirth and childrearing. I argue that, in absolute terms, women's labour market position deteriorated in the three countries in this study, but not to the extent that had been expected. In fact, women improved their positions in some areas, and their losses relative to men have-so far-been minimal. More importantly, there are significant variations across the three countries in how women fared. In Poland, a 'familial welfare state' (in which families, rather than the state have been expected to take primary responsibility for dependents), combined with a long history of women's labour-market disadvantage, assigns women primarily to the household. Women do work, of course, but unemployment is rampant, the wage gap is significant, and women seem to have difficulty gaining positions of authority in the workplace. Women are most likely to be economically active in the Czech Republic, which underwent a slower, less radical, economic transformation process, but they are found in significantly lower-level positions in the labour market: women keep working, but at a distinct disadvantage compared to men. Hungary, on the other hand, is marked by a strong bifurcation of women's positions. This differentiation exists in the other two countries as well, but the presence of a poor ethnic minority in Hungary makes social exclusion along the lines of gender (as well as race and class) more visible and also politically significant. Hungarian women in the upper-middle class-often also young, childless and highly educated-have been quite successful in gaining or retaining their positions in the labour market and fighting for social rights that help them combine these with some household responsibilities. Poor women, however, are left behind, inactive, retired early or subsisting on welfare benefits; they are discouraged from looking for work, and would have trouble fitting into the new world order.
Keywords: 330